A comprehensive review of impacts of ozone treatment on textural properties in different food products. (September 2022) - Pandiselvam, R.; Singh, Arashdeep; Agriopoulou, Sofia; Sachadyn-Król, Monika; Aslam, Raouf; Gonçalves Lima, Clara Mariana; Khanashyam, Anandu Chandra; Kothakota, Anjineyulu; Atakan, Orhan; Kumar, Manoj; Mathanghi, S.K.; Mousavi Khaneghah, Amin
Abstract: Background: The application of ozone in liquid or gaseous form in food is a green, economical, and practical technology that has attracted industry interest. The oxidation effect of ozone has antimicrobial and antiviral activity, induces starch modification, eliminates pests, and can degrade pesticides to improve food safety and quality. Texture plays a crucial role in food perception and influences the taste experience; thus, the food industry is looking for technologies that do not negatively impact products' textural and sensory characteristics. Scope and approach: In this review, the impact of ozone treatment on textural properties of various plant and animal-based foods was summarized and discussed for the first time. Key findings and conclusions: Consumer acceptance of fresh produces and/or food products is closely related to freshness and wholesomeness. The ozone concentration and exposure time are the most critical factors affecting the effectiveness of food treatment and textural properties. Hence, these ozone processing parameters need to be optimized for each product to alleviate the negative effect of ozone on food texture. Research papers highlighted that ozone is a potential technique for inactivating the fruits and vegetables' softening enzymes, which helps retain their firmness. Overall, ozone has a great potential to improve food functionality. Highlights: High oxidation potential of ozone results in significant changes to the textural attributes. Optimum ozone dose positively influence the texture of fruits and vegetables. Ozone can cause protein aggregation and fat coalescence in milk resulting in changes in textural properties.